Study about Three-Dimensional Visualization of Lithium Metal Anode via Low-Dose Cryogenic Electron Microscopy Tomography - Bing Han; Xiangyan Li; Yucheng Zou (Recent Progress in Science and Technology Vol. 1, 2023)
In this study, a method for characterizing the 3D intrinsic structure of high beam sensitive samples was established based on a low dose Cryo-EM tomography. The investigation of cycle stability or decay mechanisms depends heavily on the structure of the lithium (Li) metal anode, including the Li metal and the solid electrolyte interphase (SEI). However, due to a lack of 3D characterization techniques and the susceptibility of the Li metal anode to oxygen, moisture, and electron beams, the three-dimensional (3D) visualisation of Li metal and SEI has not yet been demonstrated. We introduce a successful 3D presentation of deposited Li metal and SEI established via low-dose cryogenic electron microscopy (Cryo-EM) tomography. The Li metal anode are imaged in low-dose mode at different tilt angles, and then aligned and reconstructed into a 3D image through an expectation-maximization algorithm. The 3D tomography of the Li metal anode confirms the spherical Li deposits and SEI. Additionally, it is found that after extended periods of rest, the Li metal corrodes and the SEI becomes concave. Researchers may need to understand the entire electrode process, identify underlying failure mechanisms, and ultimately provide a strategic solution to extend the calendar life of batteries based on the spatial characteristics of active electrode materials and electrode-electrolyte interphases.